NOTAS ADICIONALES SOBRE COSTUMBRISMO Y TEATRO EN EL SIGLO XVIII (SOBRE LA CONSTRUCCIÓN Y REPRESENTACIÓN DEL IMAGINARIO PENINSULAR) - Alberto Romero Ferrer (Cuadernos de Ilustración y Romanticismo)
The rise of costumbrismo in the eighteenth century, as a new way of looking at and reflecting peninsular life in literature, theatre —from the sainete to the tonadilla escénica—, painting and music, entail the discovery of popular reality. Moreover, an important part of this short period in the eighteenth-century theatre sets its structural features around the presence of music. The technical innovations introduced in the theatre during the Enlightenment, particularly in more serious genres, like the zarzuela, the Spanish light opera and the Italian operetta can also be traced in the short forms of one-act farce and especially in the tonadilla, a popular song. The last one will eventually develop into a sort of Spanish comic opera, but shorter. This short paper provides some additional evidences in addition to those which were presented in Romero Ferrer (2016 y 2017).